Pembaruan Special Defence dalam Tindak Pidana Pencemaran Nama Baik Melalui Media Elektronik di Indonesia (Studi Komparasi dengan Malaysia) - Nurlina Husnita (Jurnal Hukum Lex Generalis, 2022)
The level of punishment for criminal defamation through electronic media (cyber defamation) in Indonesia is quite high. This is because the Special Defence is rarely referred to in Article 310 Paragraph (3) of the Indonesian Penal Code (KUHP) and the provisions in that article are limited. This study aims to examine the renewal of criminal law related to special defense in cyber defamation crimes in Indonesia by comparing them with the provisions in force in Malaysia. This study uses qualitative juridical data analysis methods and normative juridical research methods against Law Number 11 of 2008 concerning Information and Electronic Transactions as amended in Law Number 19 of 2016, the Indonesian Penal Code (KUHP), and the Malaysian Penal Code as a material ratio. The results show that Indonesia can adopt the concept of Special Defence from cyber defamation as applicable in Malaysia, by comprehensively regulating it in UU ITE as a "lex specialis" of the Indonesian Penal Code (KUHP) that regulates cyber defamation. This is a manifestation of the benefits of comparative law as a renewal of the Indonesian criminal law system.